Bone healing in critical-size defects treated with platelet-rich plasma activated by two different methods. A histologic and histometric study in rat calvaria - Messora, M. R. [UNESP]; Nagata, Maria José Hitomi [UNESP]; Dornelles, Rita Cássia Menegati [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Furlaneto, F. A. C. [UNESP]; de Melo, L. G. N. [UNESP]; Deliberador, T. M. [UNESP]; Bosco, Álvaro Francisco [UNESP]; Garcia, Valdir Gouveia [UNESP]; Fucini, S. E. [UNESP] (Wiley-Blackwell Publishing, Inc, 2008)
The purpose of this study was to analyze histologically the influence of platelet-rich plasma (PRP) coagulated with two different activators on bone healing in surgically created critical-size defects (CSD) in rat calvaria.Forty-eight rats were divided into three groups: C, PRP-C and PRP-T. An 8 mm diameter CSD was created in the calvarium of each animal. In group C, the defect was filled by a blood clot only. In groups PRP-C and PRP-T, the defect was filled with PRP activated with either calcium chloride or thromboplastin solution, respectively. Each group was divided into two subgroups (n = 8 per subgroup) and killed at either 4 or 12 weeks postoperatively. Histologic and histometric analyses were performed. The amount of new bone formed was calculated as a percentage of the total area of the original defect. Percentage data were transformed into arccosine for statistical analysis (analysis of variance, Tukey's post hoc test, p < 0.05).No defect completely regenerated with bone. Group PRP-C had a statistically greater amount of bone formation than groups C and PRP-T at both time points of analysis. No statistically significant differences were observed between groups C and PRP-T.It can be concluded that the type of activator used to initiate PRP clot formation influences its biological effect on bone healing in CSD in rat calvaria.
Keywords: platelet-rich plasma; growth factor; coagulant; bone regeneration